2003
DOI: 10.1074/jbc.m305502200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor Activates the Transforming Growth Factor-α/Epidermal Growth Factor Receptor Growth Stimulatory Pathway in VHL-/- Renal Cell Carcinoma Cells

Abstract: These data link HIF with the overproduction of a bona fide renal cell mitogen leading to activation of a pathway involved in growth of renal cancer cells. Moreover, our results suggest that HIF might be involved in oncogenesis to a much higher extent than previously appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
142
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 66 publications
6
142
1
4
Order By: Relevance
“…Previous investigators have not reported suppression of EGFR protein after re-expression of wt-VHL (Knebelmann et al, 1998;Gunaratnam et al, 2003). However, in the report by Gunaratnam et al, (2003), adenovirus-mediated introduction of wt-VHL into 786-O cells visibly reduced EGFR levels (see their Figure 2A), although this difference was either discounted or not further clarified (Gunaratnam et al, 2003). In the report of Knebelmann et al, (1998), the Western blot appears too overexposed for optimal quantitation (Knebelmann et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous investigators have not reported suppression of EGFR protein after re-expression of wt-VHL (Knebelmann et al, 1998;Gunaratnam et al, 2003). However, in the report by Gunaratnam et al, (2003), adenovirus-mediated introduction of wt-VHL into 786-O cells visibly reduced EGFR levels (see their Figure 2A), although this difference was either discounted or not further clarified (Gunaratnam et al, 2003). In the report of Knebelmann et al, (1998), the Western blot appears too overexposed for optimal quantitation (Knebelmann et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…TGFa, an EGFR ligand under transcriptional control by HIF, is constitutively expressed in VHL mutant cells (Knebelmann et al, 1998;de Paulsen et al, 2001;Gunaratnam et al, 2003). These observations have led to clinical trials of EGFR inhibitors in RCC (Drucker et al, 2003;Motzer et al, 2003;Foon et al, 2004;Rowinsky et al, 2004;Amato, 2005).…”
mentioning
confidence: 99%
“…In that respect the majority of ccRCC, the most common subtype of renal cell cancer (RCC), bear biallelic-inactivating mutations of the VHL tumor suppressor gene [44]. As a consequence, VHL -/-ccRCC cells have a constitutive, oxygen-independent activation of HIF1α/HIF-2α [45]. Unregulated growth of these cells was reported to be promoted by activating the transforming growth factor-α (TGF-α)/EGFR pathway.…”
Section: Induction Of Rtk Ligandsmentioning
confidence: 99%
“…Unregulated growth of these cells was reported to be promoted by activating the transforming growth factor-α (TGF-α)/EGFR pathway. It was shown that overproduction of TGF-α by VHL -/-ccRCC is a direct consequence of HIF activation [45]. Notably, the use of EGFR inhibitors was as efficient as reintroducing VHL for abolishing the ability of ccRCC cells to form tumors in nude mice [46][47][48].…”
Section: Induction Of Rtk Ligandsmentioning
confidence: 99%
See 1 more Smart Citation